EFFECT OF THYROID DYSFUNCTION ON BODY MASS INDEX AND HORMONAL IMBALANCE IN WOMEN HAVING POLYCYSTIC OVARIAN SYNDROME - NADEEM, F; ASHRAF, S; ASLAM, S; IQBAL, A; BUTT, MA; ANWAR, R; IRSHAD, F (Biological and Clinical Sciences Research Journal, 2024)
Polycystic ovary syndrome (PCOS) is a prevalent gynecological disorder that significantly impacts women of reproductive age. Both PCOS and thyroid dysfunction independently increase the risk of ovarian dysfunction and prenatal complications. International studies have associated thyroid dysfunction with menstrual irregularities in women. Objective: This study aims to understand the influence of thyroid dysfunction on Body Mass Index (BMI) and hormonal imbalance in women diagnosed with PCOS. Methods: A cross-sectional study was conducted at two medical facilities, Sardar Begam Hospital and Cheema Family Hospital, involving participants aged 18 to 43 years. The sample size consisted of women diagnosed with PCOS. Data collection spanned from April 2023 to April 2024. A structured questionnaire was utilized to collect data on participants' history of PCOS, symptoms of irregular menstrual cycles, and BMI. Blood samples were collected to measure thyroid hormone levels, which were analyzed using ELISA. Statistical analysis was performed using [Insert Statistical Software], applying descriptive statistics and comparative analysis to assess the impact of thyroid dysfunction on BMI and hormone levels in PCOS patients. Results: The study findings indicate that 73.33% of women with both PCOS and thyroid dysfunction experienced weight gain, whereas only 26.67% did not report weight gain. Additionally, 80% of the participants reported acne, 60% experienced hirsutism, and 90% had irregular menstrual cycles. Muscle weakness and low energy were prevalent in 63.33% of the women, while 73.33% reported depression, and 66.67% reported hair loss. Significant differences were observed in the levels of Triiodothyronine (T3) and Thyroxine (T4) among women with PCOS with and without thyroid dysfunction. Specifically, for T3 levels, PCOS patients with thyroid dysfunction had a mean level of 7.3213, whereas those without thyroid dysfunction had a mean level of 63.812. Similarly, for T4 levels, PCOS patients with thyroid dysfunction had a mean level of 7.3213, compared to 63.812 in those without thyroid dysfunction. Conclusion: The study highlights the substantial impact of thyroid dysfunction on both T3 and T4 levels in PCOS patients. These findings underscore the importance of routine thyroid function screening in PCOS patients to devise more personalized and effective treatment strategies.